Do later-born birth cohorts of septuagenarians sleep better? A prospective population-based study of two birth cohorts of 70-year-olds. Issue 1 (24th October 2018) - Skoog, Johan; Jönsson, Helena; Sigström, Robert; Östling, Svante; Falk, Hanna; Waern, Margda; Thorvaldsson, Valgeir; Skoog, Ingmar; Johansson, Boo
Abstract: Study Objectives: To investigate birth cohort differences in the prevalence of insomnia from ages 70 to 79. Methods: Data were drawn from population-based samples of two cohorts of septuagenarians; the early-born 1901-07-cohort, who took part in psychiatric examinations between 1971 and 1986 ( n = 681), and the later-born 1930-cohort examined between 2000 and 2010 ( n = 943). Examinations were conducted at ages 70, 75, and 79. Criteria for insomnia were identical across cohorts and included sleep dissatisfaction accompanied with complaints of difficulty initiating or maintaining sleep. Associations were analyzed with logistic growth curve models. Results: The later-born cohort had lower odds for insomnia at age 70 (OR = 0.52, 95% CI: 0.32–0.87) compared with the earlier born cohort. Age was not related to insomnia as a main effect but we found an interaction between age and birth cohort (OR = 1.14, 95% CI: 1.08–1.21); insomnia increased with age in the later but not in the early-born cohort. Women had higher odds for insomnia compared with men (OR = 3.10, 95% CI: 2.02–4.74), and there was an interaction between sex and birth cohort (OR = 0.51, 95% CI: 0.30–0.88; there were larger cohort differences among women than among men and less sex differences in the later than in the earlier born cohort. Also, there were no significant differences between the cohorts in taking sleep medications. Conclusions: Our findings provide evidence of improved self-reported sleep in later-born cohorts of septuagenarians, but the difference diminished with age. The prevalence of self-reported insomnia was greater in women than in men, but sex differences were less pronounced in the later-born cohort.